DUOLINGO APPLICATION AS A TEACHING TOOL ON ENHANCING STUDENTS’ VOCABULARY KNOWLEDGE - Hardiyanti, Hardiyanti; Munir, Munir; Rahmawati, Rahmawati (JTechLP: Journal of Technology in Language Pedagogy, 2023)
This study is a quantitative research project utilizing a pre-experimental design with one group, involving both pre-test and post-test assessments. Its primary objective is to determine the impact of implementing the Duolingo Application as a teaching tool on enhancing the vocabulary knowledge of Class X.F students at SMA Negeri 1 Pinrang. In this research, the independent variable is the use of the Duolingo Application as a learning medium, while the dependent variable is the students' vocabulary knowledge. The research population encompasses all Class X students, ranging from X.A to X.L, totaling 432 students, with each class typically consisting of 33 to 35 students. The research sample specifically includes 33 students from Class F, selected through random sampling. Data for the research were collected through pre-test and post-test assessments on vocabulary topics. The data analysis involved normality tests, T-tests, and descriptive statistics. The findings indicate that the mean score of the post-test (68.18) was significantly higher than that of the pre-test (28.78), suggesting that the utilization of the Duolingo Application has positively influenced students' vocabulary knowledge. The standard deviation for the pre-test was 7.8, while for the post-test, it was 13.2. To determine whether to reject the null hypothesis, the researchers compared the p-value (0.000) to the standard level of significance (0.05). Since the p-value was less than 0.05, the null hypothesis was rejected, leading to the conclusion that the use of the Duolingo Application effectively improved students' vocabulary knowledge.